δ-Viniferin, a Resveratrol Dehydrodimer: One of the Major Stilbenes Synthesized by Stressed Grapevine Leaves - Pezet, Roger; Perret, Camille; Jean-Denis, Julien Bernard; Tabacchi, Raffaele; Gindro, Katia; Viret, Olivier (Journal of agricultural and food chemistry, 2003)
δ-Viniferin is a resveratrol dehydrodimer, an isomer of ε-viniferin. This compound has been reported as a molecule produced in vitro by the oxidative dimerization of resveratrol by plant peroxidases or fungal laccases. It was also recently identified in wines and in grape cell cultures. We have now identified this dimer by NMR, high-performance liquid chromatography−diode array detection (HPLC-DAD), and HPLC-mass spectrometry (MS) in grapevine leaves infected by Plasmopara viticola (downy mildew) or UV-C irradiated. Its concentration was higher than that of ε-viniferin and constitutes one of the most important phytoalexins derived from resveratrol. Keywords: Stilbenes; Vitis vinifera; resveratrol; viniferins; HPLC; LC-MS; NMR; UV spectra